Associations of rumination, behavioral activation, and perceived reward with mothers’ postpartum depression during the COVID-19 pandemic: a cross-sectional study - Matsunaga, Miki; Okajima, Junko; Furutani, Kaichiro; Kusakabe, Noriko; Nakamura-Taira, Nanako (Frontiers in Psychiatry, 2024)
The COVID-19 pandemic has led to increased social isolation for mothers, and rumination exacerbates postpartum depression in mothers with poor social support. Although behavioral activation can help to decrease their depressive symptoms, the mechanism by which behavioral activation reduces postpartum depression remains unclear. Method: We examined the effects of rumination and behavioral activation on depression in postpartum women by examining a model mediated by subjective reward perception. A questionnaire was administered to 475 postpartum women (Age: Mean = 30.74 years, SD = 5.02) within one year of childbirth using an Internet survey. The measurements included perinatal depression, rumination, and behavioral activation, and we assessed environmental reward. To control for confounding variables, we assessed psychiatric history, social support, parenting perfectionism, and COVID-19 avoidance. Results: Eighty-four (17.68%) mothers had possible postpartum depression. The covariance structure analysis showed that not only was there a direct positive path from rumination to postnatal depression but also a negative path via reward perception. Discussion: This finding indicated that the COVID-19 pandemic could have increased depression in many of the mothers. Rumination not only directly relates to postpartum depression, but it could also indirectly relate to postpartum depression by decreasing exposure to positive reinforcers. In addition, having a history of psychiatric illness increases the effect of rumination on postpartum depression. These findings suggest that psychological interventions are needed to reduce rumination and increase contact with positive reinforcements to reduce postpartum depression, especially for high-risk groups.